Peculiarities of Metathesis in Kunha Language - Kujur, Anup Kumar; Dash, Biswanandan (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This paper focuses on metathesis, a linguistic phenomenon observed in the unique language called Kunha, a part of the North-Dravidian language family, where sounds are swapped within words. So, instead of the anticipated order of ..xy.. in a sequence of participating sounds, we encounter ..yx.. The final segments of a word can vary depending on the context; in some cases, they appear as a vowel followed by a consonant, while in others, they may be a consonant followed by a vowel. Metathesis in the Kunha language (Odisha, India), analysing its phonological patterns and linguistic implications from a synchronic perspective. Data was collected via 5,000 lexicons and sociolinguistic interviews with NORMs in Sundergarh and Sambalpur districts of Odisha state, alongside comparisons to Kurux and Dravidian etymological sources. Theoretical frameworks categorise metathesis as (1) copy-delete/coalescence operations, (2) transposition outcomes, or (3) allomorphy-driven CV/CC/CVC rearrangements. The results focus on Kunha’s pervasive yet irregular CV/CC/CVC metathesis, previously undocumented, highlighting its typological rarity and challenges for linguistic prediction. For example, the word /oɽok/ ‘bark of a tree’ in Kurux, changes to /uɽku:/ in Kunha. Similarly, /calkur/ ‘sand, gravel’ in Kurux, transforms to /calkri:/ in Kunha. These peculiarities in sound change are not limited to CV (consonant-vowel) clusters; they also occur in CC (consonant-consonant) clusters. For instance, /maːkcuːɳɖ/ ‘name of a flower’ in Kurux, changes to /maːskuːɽ/ in Kunha, resulting in the sound change from [kc] to [sk]. Additionally, metathesis can affect CVC (consonant-vowel-consonant) order, as seen in the transformation of /letheɽ okk-aː/ ‘to sit with the legs crossed’ in Kurux, into /thepeɽ okk-aː/ in Kunha, yielding the change from [leth] to [thep]. Due to these sound transpositions, there is an emergence of a new speech variety called Kunha.